Evolution of Host Target Cell Specificity During HIV-1 Infection - Council, Olivia D.; Joseph, Sarah B. (Current HIV Research, 2018)
Background: Many details of HIV-1 molecular virology have been translated into lifesaving antiviral drugs. Yet, we have an incomplete understanding of the cells in which HIV-1 replicates in untreated individuals and persists in during antiretroviral therapy. Methods: In this review we discuss how viral entry phenotypes have been characterized and the insights they have revealed about the target cells supporting HIV-1 replication. In addition, we will examine whether some HIV-1 variants have the ability to enter cells lacking CD4 (such as astrocytes) and the role that trans-infection plays in HIV-1 replication. Results: HIV-1 entry into a target cell is determined by whether the viral receptor (CD4) and the coreceptor (CCR5 or CXCR4) are expressed on that cell. Sustained HIV-1 replication in a cell type can produce viral lineages that are tuned to the CD4 density and coreceptor expressed on those cells; a fact that allows us to use Env protein entry phenotypes to infer information about the cells in which a viral lineage has been replicating and adapting. Conclusion: We now recognize that HIV-1 variants can be divided into three classes representing the primary target cells of HIV-1; R5 T cell-tropic variants that are adapted to entering memory CD4+ T cells, X4 T cell-tropic variants that are adapted to entering naïve CD4+ T cells and Mtropic variants that are adapted to entering macrophages and possibly other cells that express low levels of CD4. While much progress has been made, the relative contribution that infection of different cell subsets makes to viral pathogenesis and persistence is still being unraveled.
Keywords: coreceptor